Amazon Hacks - Bausch, Paul (O'Reilly, 2011)
Amazon Hacks is a collection of real-world tips, tricks, and full-scale solutions to practical uses of Amazon.com and the Amazon Web Services API . The book offers a variety of interesting ways for power users to get the most out of Amazon and its community, for Associates to hone their recommendations for better linking and more referral fees, for researchers to mine the enormous amount of information in Amazon's data store, and for developers to integrate Amazon Web Services into their applications and services.